Populism and Folklorism in Central European Music Pedagogy of the Nineteenth and Early Twentieth Centuries (Journal of the Society for Musicology in Ireland, 2009)
The nineteenth century saw the beginnings of a fascination for ‘naïve’ folk art as a supposed encapsulation of ‘national spirit’, a fascination which juxtaposed and frequently intersected with a growing interest by many composers in the creation of didactic art music for children. Folk themes, considered ‘child-like’ and ‘pure’ in character, informed many of these works because of their apparent aptness for a young audience. Such works led to a populist trend peaking in the early twentieth century that saw composers using everyday folk-art themes and references, in the context of their own compositional idiom, as a means of introducing not only children but the general public to arcane principles of art music in an accessible way.Bound up with the populist concern for the musical education of ‘the masses’ (through reference to ‘their’ folk-music genres) were topical social and political ideologies, chiefly nationalism and later, at the start of the twentieth century, evolutionism, which influenced the composers’ selection of folk-music themes for their pedagogical works and were clearly evident in their explanatory literature about this music. Through reference to composers from Schumann to Kodály and Orff, this article traces the development and influence of the Volk concept, from both nationalist and evolutionist perspectives, on Central European musical pedagogy of the nineteenth and early twentieth centuries.